O Simples Nacional e o princípio do tratamento favorecido na Constituição Econômica do Brasil: uma análise à luz da reforma tributária de 2023 - Viana, Hudson Andrade (2024)
This work reflects on the Simples Nacional, as a unified special regime for the collection of taxes and contributions owed by microenterprises and small businesses, and the potential impacts arising from the recent tax reform implemented by Constitutional Amendment No. 132/2023. One of the guiding pillars of the tax reform is the pursuit of simplifying the national tax system, which aims to be achieved through the creation of the VAT (Value Added Tax), composed of the IBS (Tax on Goods and Services) and CBS (Contribution on Goods and Services), replacing five currently existing consumption taxes: ICMS, ISS, PIS, Cofins, and IPI. Another pillar of the reform is the neutrality of the tax burden, resulting from the non-cumulative technique, which allows for the crediting of taxes paid on the acquisition of goods and services in the previous stage of the production chain. However, Constitutional Amendment No. 132/2023 stipulates that Simples Nacional optants can only benefit from the noncumulativity of taxes if they choose to pay the IBS and CBS outside the simplified unified regime. Thus, this work aims to analyze whether the adoption of a hybrid tax regime by micro and small businesses respects the principles outlined in Brazil's Economic Constitution, especially those of preferential treatment for small businesses and free competition. To achieve this goal, bibliographic research, jurisprudence, and legislation were conducted using the deductive method and qualitative approach. It was concluded that the system outlined by the reform may increase compliance costs for Simples Nacional optants, conflicting with the principles of the Constitutional Economic Order.